Water-holding capacity and instrumental texture properties of m. Longissimus dorsi and m. Serratus ventralis from Iberian pigs as affected by the production system (Livestock Science, 2012)
Meat from Iberian pigs had a high quality and an important acceptance for consumers, but is affected enormously by production conditions. So, in this study, ninety Iberian pigs were randomly allotted into three batches – Montanera (free-range rearing and fed on acorns and grass), Intensive (conﬁnement rearing and fed on concentrate) and Recebo (free-range rearing fed on acorn, grass and concentrate) – in order to characterize the inﬂuence of the production system on water holding capacity (WHC), drip loss, thaw loss and cook loss and instrumental texture traits of m. Longissimus dorsi and m. Serratus ventralis. Muscles from pigs raised in Montanera had greater WHC and lower water losses after thawing than those from Intensive system. Instrumental texture analysis showed that muscles from Montanera pigs had different characteristics as determined by instrumental Texture proﬁle analysis (TPA) and with most resistance to cutting of the muscle ﬁbres Warner–Bratzler (W–B). In all the cases, however, the type of muscle showed a different behaviour on water loss and rheological properties. So, these results suggest that meat quality of Iberian pig is highly inﬂuenced by the production system and type of muscle studied.